2010
DOI: 10.4088/jcp.08m04787blu
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Trauma Load andSLC6A4Promoter Polymorphism in Posttraumatic Stress Disorder

Abstract: We find evidence for a gene-environment interplay for PTSD and show that genetic influences lose importance when environmental factors cause an extremely high trauma burden to an individual. In the future, it may be important to determine whether the effectiveness of therapeutic interventions in PTSD is also modulated by the SLC6A4 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 36 publications
3
94
1
6
Order By: Relevance
“…This is consistent with previous studies showing that the S allele of 5-HTTLPR may be an independent risk factor for depression (Lee et al, 2005). The S allele is also positively correlated with post-traumatic stress disorder incidence rate (Kolassa et al, 2010). The L allele may be a protective factor and can reduce the incidence of depression (Grabe et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies showing that the S allele of 5-HTTLPR may be an independent risk factor for depression (Lee et al, 2005). The S allele is also positively correlated with post-traumatic stress disorder incidence rate (Kolassa et al, 2010). The L allele may be a protective factor and can reduce the incidence of depression (Grabe et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…transporter (SLC6A4) locus [34] and the catechol-Omethyltransferase (COMT) locus [35]. Although the prevalence of PTSD approached 100% when traumatic exposure reached extreme levels in both studies, those homozygous for the short SLC6A4 promoter allele showed 100% probability of PTSD independent of number of traumatic events [34]; and those homozygous for the Met COMT allele showed a high risk of PTSD even with small traumatic loads [35].…”
Section: Discussionmentioning
confidence: 92%
“…Our detection of a significant interaction between MAN2C1 methylation and participants' exposure to potentially traumatic events adds to a small but growing literature examining the joint and interacting ways in which molecular factors and cumulative traumatic burden may modify risk for PTSD. Recent work by Kolassa and colleagues [34,35] has focused on survivors of the Rwandan genocide and risk for PTSD in light of genetic variation at two distinct loci: the serotonin Table 2 of [19]. * * = p < 0.01 PTSD vs. control.…”
Section: Discussionmentioning
confidence: 99%
“…Because the dopaminergic and adrenergic systems are also implicated in stress and fear biology, variation in dopamine regulating genes (e.g., dopamine β-hydroxylase, dopamine transporter and DRD2 genes) has been investigated in association with PTSD [22][23][24][25][26][27][28]. Variation in the serotonin transporter gene has been widely studied in association with PTSD [29][30][31] and in particular in the context of gene by environment studies [32][33][34] (see below for further discussion of this type of design). The interested reader is referred to recent reviews of genetic association studies in PTSD for further details [35,36].…”
Section: Gene Association Studies In Ptsdmentioning
confidence: 99%
“…Not only are levels of severity important with respect to a focal trauma, but cumulative effects of a lifetime of experiences. For example, whether the low expression allele in the promoter region of the serotonin transporter gene is associated with risk of PTSD depends on both individual-level trauma exposure severity [30] and macro-social context [33].…”
Section: Genes and Environment Jointly Predict Ptsdmentioning
confidence: 99%